KONSEP PENINGKATAN KUALITAS PENANGANAN PERMUKIMAN KUMUH KEL. SEPANJANG JAYA, KEC. RAWA LUMBU, KOTA BEKASI: indonesia - Wiyoga Triharto (J-ENSITEC, 2022)
The problem of slum settlements in Indonesia is still the main problem faced in residential areas in cities and districts. The problem of slum settlements is the main issue in Bekasi City. which is quite a polemic with urban problems, high levels of density and heterogeneous activity functions. The purpose of the study was to identify the condition of the slum area of ​​Bekasi City in the Panjang Jaya Village, Rawa Lumbu District to get a concept of improving the quality of handling slum settlements, by analyzing the infrastructure service needs of the slum area and the conditions of settlements in the slum area. The research methodology uses qualitative descriptive methods through primary and secondary data collection by survey and interview methods. To obtain in-depth data and examine slum settlements, this research uses a normative, participatory and facilitative approach.